The Finest Blend Graduate Education in Canada - Parchoma, Gale; Power, Michael; Lock, Jennifer (Athabasca University Press, 2020)
As Canadian universities work to increase access to graduate education, many are adopting blended modes of delivery for courses and programs. Within this changing landscape of higher education, The Finest Blend answers the call for rigorous research into these methods to ensure quality learning and teaching experience and presents case studies of French and English universities across Canada that are experimenting with blended learning models in graduate programs. Drawing on various research methods, the contributors to the volume investigate the sustainability of blended learning, shifts in pedagogical practices, and the role of instructional designers. They share key practices for both graduate students and instructors and emphasize the importance of institutional and departmental support for both students and faculty transitioning to blended delivery modes. Touching on theory, design, delivery, facilitation, administration, and evaluation, this book provides a comprehensive overview of current practices and opportunities for blended learning success. With contributions by Alicia Adlington, Shaily Bhola, Denise Carew, Jane Costello, Daph Crane, Jane Hanson, Michael Fairbrother, Wendy Kraglund-Gauthier, Shehzad Ghani, Michele Jacobsen, Carol Johnson, Sawsen Lakhal, Yang (Flora) Liu, Dorothea Nelson, Pam Phillips, Marlon Simmons, Kathy Snow, Maurice Taylor, and Jay Wilson.